2010
DOI: 10.1039/c000689k
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-occupational exposure to polycyclic aromatic hydrocarbons through personal air sampling and urinary biomonitoring

Abstract: Non-occupational inhalation and ingestion exposure to polycyclic aromatic hydrocarbons (PAHs) has been studied in 8 non-smoking volunteers through personal air sampling and urinary biomonitoring. The study period was divided into 4 segments (2 days/segment), including weekdays with regular commute and weekends with limited traffic related exposures; each segment had a high or low PAH diet. Personal air samples were collected continuously from the subjects while at home, at work, and while commuting to and from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 62 publications
0
56
0
Order By: Relevance
“…3 Furthermore, inhalation is the dominant exposure route for small PAHs such as NAP in general population. 39,40 For most FLU, PHE and PYR metabolites, the amount of OH-PAHs excreted within 24 h after the dietary exposure was correlated or marginally correlated with the amount of ingested barbecued chicken, and thus, correlated with the amount of ingested PAHs. This is encouraging, especially considering the small sample size (9 participants or N=9).…”
Section: Excreted Metabolite Amounts In Comparison To Ingested Pahsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Furthermore, inhalation is the dominant exposure route for small PAHs such as NAP in general population. 39,40 For most FLU, PHE and PYR metabolites, the amount of OH-PAHs excreted within 24 h after the dietary exposure was correlated or marginally correlated with the amount of ingested barbecued chicken, and thus, correlated with the amount of ingested PAHs. This is encouraging, especially considering the small sample size (9 participants or N=9).…”
Section: Excreted Metabolite Amounts In Comparison To Ingested Pahsmentioning
confidence: 99%
“…Similar 1-NAP-specific spikes have also been observed in several previous studies on non-occupationally exposed reference populations. 34,40 Considering the wide usage of the carbaryl pesticides and its dominant contribution to urinary 1-NAP when exposed, we recommend not using 1-NAP, and relying on 2-NAP instead as the biomarker to naphthalene exposure in future biomonitoring studies.…”
Section: Urinary 1-nap: Pesticide or Pah Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…Inhalation has been thought to be a major route of human exposure to PAH because of the presence of high level PAHs in the atmosphere (ATSDR 1995;Li et al 2010). Atmospheric PAHs can be present in particulate matters or gas phase, depending on the different vapor pressure of PAH congeners (Chang et al 2006;Park et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, PAHs can be hydroxylated by CYP450-oxidases, which is a key step in the activation process to produce the polar biochemically reactive electrophilic species (ultimate carcinogenic metabolites) capable of interacting with cellular macromolecules, particularly nucleic acids and proteins (Zhou et al, 2003). Most recently, hydroxylated PAHs (HO-PAHs) have emerged and are causing increasing concern due to their detection in human hair (Schummer et al, 2009), urine (Campo et al, 2010Li et al, 2010c), and expired air samples (Li et al, 2010c); these agents have even been found in the bile of deep-sea fish (Escartin and Porte, 1999). Previous studies have shown that certain HO-PAHs can affect hormone homeostasis, as they act as potent ligands for binding to the aryl hydrocarbon receptor (AhR) and even interact with DNA (Wang et al, 2009a;Wenger et al, 2009;Ohura et al, 2010;Wei et al, 2010).…”
Section: Introductionmentioning
confidence: 99%